Multiparameter imaging of calcium and abscisic acid and high‐resolution quantitative calcium measurements using R‐GECO1‐mTurquoise in Arabidopsis. Issue 1 (October 2017) - Waadt, Rainer; Krebs, Melanie; Kudla, Jörg; Schumacher, Karin
Summary: Calcium signals occur in specific spatio‐temporal patterns in response to various stimuli and are coordinated with, for example, hormonal signals, for physiological and developmental adaptations. Quantification of calcium together with other signalling molecules is required for correlative analyses and to decipher downstream calcium‐decoding mechanisms. Simultaneous in vivo imaging of calcium and abscisic acid has been performed here to investigate the interdependence of the respective signalling processes in Arabidopsis thaliana roots. Advanced ratiometric genetically encoded calcium indicators have been generated and in vivo calcium calibration protocols were established to determine absolute calcium concentration changes in response to auxin and ATP. In roots, abscisic acid induced long‐term basal calcium concentration increases, while auxin triggered rapid signals in the elongation zone. The advanced ratiometric calcium indicator R‐GECO1‐mTurquoise exhibited an increased calcium signal resolution compared to commonly used Förster resonance energy transfer‐based indicators. Quantitative calcium measurements in Arabidopsis root tips using R‐GECO1‐mTurquoise revealed detailed maps of absolute calcium concentration changes in response to auxin and ATP. Calcium calibration protocols using R‐GECO1‐mTurquoise enabled high‐resolution quantitative imaging of resting cytosolic calcium concentrations and their dynamic changes that revealed distinct hormonal and ATP responses in roots.